(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Community-based tourism village development is an important strategy for improving the welfare of local communities while preserving cultural and environmental sustainability. This study aims to analyze the development strategies of the Randuagung Tourism Village based on community participation, the forms and levels of community involvement, as well as the obstacles and challenges faced in its development. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research informants include village government officials, tourism village managers, tourism business actors, the Village Community Empowerment Institution (LPMD), and local community members. The results show that the development strategy of Randuagung Tourism Village focuses on utilizing local potential, including Kebun Winih Tourism, Kebun Oppa, and Sumber Suko, through a management approach that actively involves the community. Community participation is reflected in involvement in tourism activities, business management, and social and cultural activities, although the level of participation remains uneven. The main challenges in developing the tourism village include limited human resources, differences in interests among stakeholders, and the underdeveloped institutional capacity of the tourism village. This study concludes that community-based tourism development in Randuagung Village requires institutional strengthening, capacity building for local communities, and strong commitment among stakeholders to ensure sustainable development